Exploring the nexus between inflation and globalization under inflation targeting through the lens of New Zealand's experience - Ayşe Kabukçuoğlu; Enrique Martínez-García; Mehmet Ali Soytaş (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
We investigate empirically the inflation dynamics in New Zealand, a small open economy and a pioneer in inflation targeting, under various open-economy Phillips curve specifications. Our forecasting exercise suggests that open-economy Phillips curves under standard measures of global slack do not help forecast domestic inflation, possibly indicating measurement problems with global slack itself. In turn, under a stable inflation target we still find that (i) global inflation or (ii) global inflation or oil prices have information content for headline CPI and core CPI inflation over the 1997:Q3-2015:Q1 period and appear to be reliable proxies for global slack in forecasting inflation.
Keywords: C21; C23; C53; F41; F47; F62; 330; Inflation Dynamics; Open-Economy Phillips Curve; Inflation Targeting; Inflation Forecasting